Pemberian Makanan Pendamping ASI (MPASI) dan Status Gizi Balita di Kelurahan Tuak Daun Merah - Asweros Umbu Zogara (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
Background. Traditionally, malnutrition is influenced by food availability in the community, weak economic development, poverty, climate issues, and war, and other contributing factors, such as the number of family members, the pattern of feeding and the prevalence of high infectious diseases. Another factor affecting the occurrence of malnutrition in infants is complementary feeding/MPASI. Feeding too early is 3.2 times can cause malnutrition. The timing of complementary feeding (MPASI) is also related to the occurrence of stunting. Objective. To find out the description of complementary feeding (MPASI) and nutritional status of infants in Tuak Daun Merah Village. Method. A cross sectional study was used for this research. It was conducted in the Village of Tuak Daun Merah, Kupang City. The research started from January to July 2018. The population of this research was mothers of infants aged 6-24 months with a total 193 people and samples amounting to 66 people. Sampling used simple random sampling technique. Results. Female (57.6%) respondents are more than men (42.4%). Most of the respondents were in the age group of 12-24 months (63.7%). There was 2 severe malnutrition status of new-born babies (baby under 2 months) who got an early MPASI and 6 babies have malnutrition; 3 babies who received an early MPASI have very short body of their nutritional status, while 11 babies experience short nutrition; and 1 baby who got an early MPASI has a very underweight nutritional status while 5 babies are underweight. Conclusion. Infants who got an early MPASI can have a negative impact on their growth and development. Every mother should be aware of the importance of giving MPASI on time and giving a nutritious food to prevent children from nutritional problems. Keywords: early complementary feeding, infants, nutritional status